Reproduction of 'Typical' gender roles in temporary organizations—No surprise for whom? The case of cooperative behaviors and their acknowledgement. Issue 1 (March 2016) - Sieben, Barbara; Braun, Timo; Ferreira, Aristides I.
Highlights: We show that in our sample of project members: The self-reported enactment of cooperative behaviours does not vary by gender. But the relation to outcomes does: Men are rewarded for displaying male typed PCB-O and not for displaying female-typed PCB-I. Women are rewarded for displaying female typed PCB-I and not for displaying male-typed PCB-O. Women are rewarded less for their PCB than men. These relations hold for both women and men in gender-congruent and gender-incongruent project roles. Abstract: Temporary organizations such as projects are known to differ in various respects from permanent ones and have been argued to be more gender-neutral. Inspired by gender research in permanent organizations, we show that (in)congruency between gender and project roles evokes similar mechanisms in both permanent and temporary systems. Using the example of cooperative behavior, operationalized as project citizenship behavior (PCB), we examine how temporary organizations reward such behaviour. A cross-sectional study was conducted, with 241 project managers and workers participating. The results of seven structural equation models reveal that though the enactment of PCB does not vary by gender, the relationship of PCB with its outcomes does: men and women were clearly rewarded differently depending on the gender congruency of their project roles.